Engineered Human Cardiac Microtissues: The State-of-the-(He)art. (15th April 2021) - Soon, Kayla; Mourad, Omar; Nunes, Sara S.
Abstract: Due to the integration of recent advances in stem cell biology, materials science, and engineering, the field of cardiac tissue engineering has been rapidly progressing toward developing more accurate functional 3D cardiac microtissues from human cell sources. These engineered tissues enable screening of cardiotoxic drugs, disease modeling (eg, by using cells from specific genetic backgrounds or modifying environmental conditions) and can serve as novel drug development platforms. This concise review presents the most recent advances and improvements in cardiac tissue formation, including cardiomyocyte maturation and disease modeling. Abstract : Recent advances in cardiac microtissue engineering with a focus on approaches to recapitulate the adult heart and model disease phenotype. The microtissue platform depicted may not be representative of platform used in selected publication and is only a generalization.